Respon Pertumbuhan Kelapa Sawit Bibit ( Elaeis guineensis Jacq.) Terhadap Jenis fungi mikoriza arbuskula pada Dua Tingkat Pemupukan NPK - Damayanti, Novri Dwi; Rini, Maria Viva; Evizal, Rusdi (Politeknik Negeri Lampung., 2015)
Oil palm (Elaeis guineensis Jacq.) is one of the important excellent crop plantations which have significance for the development of national farm and country source of foreign exchange earnings.Oil palm cultivation is mostly done on the ground of ultisol that have constraints phosphorus deficiency that needed improvement in the quality of the nursery with the utilization of arbuscular mycorrhiza fungi (AMF). The study aimed: (1) determine the best type of AMF in enhancing the growth of oil palm seedlings, (2) determine dose of NPK fertilize most appropriate for the oil palm seedling, (3) determine whether the response of oil palm seedlings to type AMF influenced by dose NPK fertilizer, and (4)determine the best dose of NPK fertilizer for each type of AMF. The treatment design is a factorial (6x2) arranged in randomize completely block design with 5 replications. The first factor is the type of AMF, design as without AMF, Glomus sp. Isolate MV 23, Glomus sp. Isolate MV 26, Entrophospora sp. Isolate MV 22, Entrophospora sp. Isolate MV 25, Entrophospora sp. Isolate MV 28.The second factor is number of NPK fertilize design as p1 (100 % from recomendation) and p2 (50 % from recomendation). Means homogeneity among the treatments were tested using Barlett test and the aditivity data were tested with Tukey test. Separation of means value were analyzed using Least Significant Difference (LSD) at 5% significance level. The results showed the interaction between the type and dose of NPK fertilizer AMF is can be concluded that (1) oil palm seedlings response to AMF inoculation type is determined by the dose of NPK fertilizer on the variable plant height, dry weight of root, and number of primary roots, 2) the optimum dose for each type of AMF are used based on the data root dry weight is a combination of 100% NPK fertilizer with each type of AMF, excepton the AMF types Entrophospora sp. Isolates MV 22. Keywords: Growth Response, Oil Palm Seedling, Arbuscular Mycorrhizal